The Role of Marine Security Agency (BAKAMLA) As Sea and Coast Guards in Indonesian Water Jurisdiction - Rika Kurniaty; Herman Suryokumoro; Setyo Widagdo (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
The Indonesian geographical condition as an archipelagic state with abundant natural resources has put maritime security into its central issue. Several challenges are facing Indonesia’s maritime coordination. National maritime agencies are still overlapping and duplicating based on various laws and regulations. As part of the Indonesian vision to be a ‘global maritime fulcrum,’ Indonesia’s government established the Marine Security Agency (BAKAMLA). BAKAMLA aims to shift the law enforcement paradigm from a multi-agency multi-task to a single-agency multi-task. The establishment of BAKAMLA is expected to create law enforcement’s effectiveness and efficiency in Indonesia’s water jurisdiction. This study is a type of normative juridical research using a statute approach and case study approach. This study reveals that the emerging of BAKAMLA, based on Law Number 32 of 2014 concerning Marine, grants broad authority to the maritime security agency. BAKAMLA has the power to direct instant pursue, dismiss, inspect, arrest, carry, and deliver the ship to the related authorized agency for further legal proceedings. BAKAMLA also has the authority to integrated security and safety information systems. The presence of BAKAMLA does not necessarily disregard or eliminate other institutions in the same task, but as a guard to stimulate to synergize further the security and safety of Indonesia’s territorial waters under a single command unit.